Numerical method for nonlinear two-phase displacement problem and its application - 彭益让 梁栋 芮洪兴 杜宁 王文洽 (Applied mathematics and mechanics, 2008)
For the three-dimensional nonlinear two-phase displacement problem, the modified upwind finite difference fractional steps schenles were put forward. Some techniques, such as calculus of variations, induction hypothesis, decomposition of high order difference operators, the theory of prior estimates and techniques were used. Optimal order estimates were derived for the error in the approximation solution. These methods have been successfully used to predict the consequences of seawater intrusion and protection projects.